The role of satellite accounting in expanding the System of National Accounts - James Tebrake (Eurostat Review on National Accounts and Macroeconomic Indicators (EURONA), 2020)
In recent years, there has been a rapid increase in the number of satellite accounts produced by national statistical organisations. The aim of this paper is to help understand the reasons for this increase and identify the need for further guidance and coordination. The paper presents the role of satellite accounting in the broader framework of the System of National Accounts (SNA) and suggests a typology that can be used to classify the different satellite accounts. Further, the paper provides a summary of international activities related to satellite accounting and a detailed overview of national practices collected through a survey which gathered responses from more than 80 countries. Finally, the paper identifies recommendations and possible next steps regarding the future development of satellite accounting and discusses the (potential) role of the international statistical community in improving this national accounting tool.
Keywords: E01; E16; 330; System of National Accounts; satellite accounts